Adaptive responses of neuromuscular system to training - Gollhofer, A. (ISBS - Conference Proceedings Archive (Konstanz), 2005)
Adaptive responses of neuromuscular system to training Contractile strength training has been investigated in a large variety of training designs. The purpose was to better understand the adaptive mechanisms of the human movement system to physical activity. In principle, for classical strength training two modalities of functional adaptations can be substantiated from those studies: Strength training can either lead to enhancements in the contractile muscular properties of the protein structures themselves or can lead to improvements in the neural supply of the contracting muscle or muscle group. Each type of adaptation can be addressed specifically by the design of the training program, basically substantiated by the height of the training load, volume of training session and duration. Evidence has been produced, that training with relatively high number of repetitions within one set (i.e. 6-15 maximum repetition (RM) load), associated with an extensive exhaustion of the trained muscle group is preferentially followed by an enhancement in strength and power. Athletes working with this methods show adaptations in the muscular tissue, enhanced cross-sectional areas, altered pinnation angles and high endocrine involvement (Rutherford and Jones, 1992; Walker et al., 1998). However, many studies report also improvements in strength and in power capabilities after strength training without a substantial adaptation of the muscular profile. Thus, an alternative functional response modality must be considered. In recent publications evidence has been produced that spinal and supraspinal mechanisms can be drastically enhanced by a specific type of training. In contract to the muscular adaptations after training with high number of RMs, neuronal adaptation is associated with training using low number of repetitions (1-8 RM load), high loads, intensive or explosive type of contraction and sufficient long periods between sets. The present paper is focused on the neuromuscular adaptive mechanisms that may come along with intensive strength training and with sensorimotor training. The motoneuron in the spinal cord is in latest consequence directly linked to the muscle fibres. Due to the fact that the functional properties of the motor units (MU) are directly dependent on the discharge characteristics of the activating spinal motoneuron, it appears logical to separate the various adaptive responses of the neuromuscular system to training in accordance to the different modalities of training.